Wood-inspired multi-channel tubular graphene network for high-performance lithium-sulfur batteries. (November 2018) - Li, Changxia; Yu, Jingyi; Xue, Shi-Lei; Cheng, Zhihua; Sun, Guoqiang; Zhang, Jing; Huang, Rudan; Qu, Liangti
Abstract: Hierarchical porous structure plays a vital role in various energy storage systems. Herein, a wood-inspired multi-channel tubular graphene (MCTG) architecture is fabricated by template-directed chemical vapor deposition (CVD). The multi-channel template is assembled via a facile hydrothermal and freeze-drying method with Si as precursor. The unique multi-channel tubular graphene architecture reveals distinct advantages for lithium-sulfur (Li-S) batteries. The curved tubular interior space with a pore volume of 2.141 cm 3  g −1 can accommodate active sulfur and anchor soluble polysulfides, while the 3D multi-channel network favors rapid mass transport and ion diffusion. Furthermore, the CVD grown few-layer graphene offers good electron conductivity, while the enlarged (002) spacing (0.35–0.41 nm) of graphene layers provide more space for sulfur storage and Li + diffusion. Benefiting from these merits, the MCTG/S cathode (loaded with 70 wt% sulfur) achieves a high initial discharge capacity of 1390 mAh g −1 at 0.1 C rate, excellent rate capability up to 8 C and a slow capacity decay rate of 0.078% per cycle during 500 cycles. This type of MCTG will also play an important role in gas adsorption, solar steam generation, catalysis, and so on. Graphical abstract: Image 1